Pengembangan Learning Card untuk meningkatkan kerja sama tim dan pengetahuan mahasiswa: A Literature Review - Elsye Maria Rosa; Nastain Abubakar Pattimura (Citra Delima Scientific journal of Citra Internasional Institute, 2021)
The use of pictorial Learning Cards aims to make it easier for students to provide associations with concepts and materials so that the images that students get can generate creative ideas. The pictorial kick card is expected to improve students' spatial and visual abilities. The purpose of this Literature Review is to review articles that examine Learning Card Development towards Improving Student Teamwork and Knowledge. The data used comes from journals that contain the concepts under study. The data collection process was carried out by filtering from 17,071 literary sources to 7 literatures based on the criteria determined by the author of each journal taken. The criteria referred to include the year the literature sources were taken from 2016 to 2019, the suitability of writing keywords, the relationship between the results of writing and discussion. Strategies in collecting journals for various literatures using accredited journal sites such as Google Scholar, Science Direct and BMC Medical Education. An effective way of writing for journal settings is by entering keywords according to the writing title such as "Learning Card AND Teamwork AND Knowledge. On the Learning card is a card that contains keywords in learning that are used by students in preparing solutions, concepts and problem solving both sequentially and systematically.